Impact of an Education-Based Antimicrobial Stewardship Program on the Appropriateness of Antibiotic Prescribing: Results of a Multicenter Observational Study - Federica Calò; Lorenzo Onorato; Margherita Macera; Giovanni Di Caprio; Caterina Monari; Antonio Russo; Anna Galdieri; Antonio Giordano; Patrizia Cuccaro; Nicola Coppola (Antibiotics, 2021)
To evaluate the effect that an education-based Antimicrobial stewardship program (ASP) implemented in two hospitals in southern Italy had on the quality and appropriateness of antibiotic prescription. We conducted a multicenter observational study in two hospitals in the Campania region. Only some departments of both hospitals were already participating in the ASP. We collected data on all patients admitted on the day of evaluation in antibiotic therapy or prophylaxis through a case report form. The primary outcome was to investigate the difference in the appropriateness of the antibiotic prescriptive practice in the departments that had joined the ASP and in those that had not participated in the project (non-ASP). The total number of patients assessed was 486. Of these, 78 (16.05%) were in antibiotic prophylaxis and 130 (26.7%) in antibiotic therapy. The prescriptive appropriateness was better in the units that had joined ASP than in those that had not, with respectively 65.8% versus 22.7% (p < 0.01). Patients in the non-ASP units more frequently received unnecessary antibiotics (44.9% versus 0%, p = 0.03) and, as surgical prophylaxis, the use of antibiotics not recommended by the guidelines (44.2% versus 0%, p = 0.036). Multivariable analysis of the factors associated with prescriptive appropriateness identified ASP units (p = 0.02) and bloodstream or cardiovascular infections (p = 0.03) as independent predictors of better prescriptive appropriateness. The findings of the present study reinforce the importance of adopting an educational ASP to improve the quality of antimicrobial prescription in clinical practice.